1993
DOI: 10.1159/000175942
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic and Prognostic Significance of Echo-Doppler-Proven Mitral Regurgitation in Patients with Dilated Cardiomyopathy

Abstract: Data from cardiac catheterization at rest and during exercise in 57 patients with dilated cardiomyopathy (DCM) were analyzed to evaluate the bearing of mitral regurgiation (MR) detected by color Doppler echocardiography (CDE) on prognostically important invasive hemodynamic parameters and survival. The etiology of DCM was coronary artery disease in 21 patients and unproven (‘idiopathic’) in 36 patients. MR was detected by CDE in 34 patients (60%) with an agreement of 93% compared to left ventriculography. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 11 publications
3
49
0
4
Order By: Relevance
“…It should enable selection of prognostic poor patients with acceptable sensitivity, on the other hand using of three objective parameters together contributes to the presumption of a good selection specificity. Similar to other authors we observed a difference between the patients of the two groups characterized by the tissue Doppler parameters of left ventricle longitudinal function during rest and after exercise, by the ratio E/Em, indexed left ventricle volume and the level of mitral regurgitation 5,11,[27][28][29] . In both of our models the only independent echocardiographic predictor of a poor prognosis, similarly to other published data 5,11 , was the parameter E/Em (during rest or after exercise).…”
Section: Discussionsupporting
confidence: 90%
“…It should enable selection of prognostic poor patients with acceptable sensitivity, on the other hand using of three objective parameters together contributes to the presumption of a good selection specificity. Similar to other authors we observed a difference between the patients of the two groups characterized by the tissue Doppler parameters of left ventricle longitudinal function during rest and after exercise, by the ratio E/Em, indexed left ventricle volume and the level of mitral regurgitation 5,11,[27][28][29] . In both of our models the only independent echocardiographic predictor of a poor prognosis, similarly to other published data 5,11 , was the parameter E/Em (during rest or after exercise).…”
Section: Discussionsupporting
confidence: 90%
“…[13][14][15][16] Chronic MR leads to progressive heart failure status through a vicious circle of LV dilatation leading to MR leading to further LV dilatation. In addition to the mechanical process, neurohormonal overload is thought to hasten the deaths of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…12) Furthermore, patients with heart failure and LV dilatation often have functional mitral regurgitation (MR), and the presence of MR is also known to be associated with a poor clinical outcome. [13][14][15][16] Although patients with D-HCM have been reported to show diverse clinical expression, there is little information on the relations among LV size, presence of significant MR, and prognosis. This study was performed to determine whether echocardiographic assessment of LV size and MR provides incremental prognostic information for patients with D-HCM.…”
mentioning
confidence: 99%
“…FMR is associated with decreased survival in patients with left ventricular systolic dysfunction and the mortality increases in parallel with the severity of FMR (1)(2)(3)(4). A number of mechanisms play role in the development of FMR.…”
Section: Introductionmentioning
confidence: 99%